Optimized Integration of Hybrid Renewable Sources with Long‐Life Battery Energy Storage in Microgrids for Peak Power Shaving and Demand Side Management under Different Tariff Scenario. Issue 9 (21st July 2021) - Bhattacharjee, Ankur; Samanta, Hiranmay; Ghosh, Aritra; Mallick, Tapas K; Sengupta, Samarjit; Saha, Hiranmay
Abstract : Herein, a novel cost‐effective demand side management and peak power shaving are demonstrated by optimized scheduling of renewable energy source integrated grid‐connected hybrid microgrid and vanadium redox flow battery (VRFB) storage. To promote the waste to energy for the rural and urban communities, the biogas energy source is integrated along with the combined solar photovoltaic (PV) and wind energy sources. As a long life and scalable battery storage solution, VRFB storage is adopted for peak shaving and microgrid performance reliability. Power generation from the renewable sources, VRFB charge–discharge, and grid power usage are scheduled considering two practical electricity tariff profiles, thus making the overall microgrid system operation cost‐effective and efficient. The optimized cost of energy management is determined considering the operation and maintenance cost of energy source and battery storage, grid tariff profile, and power import and export. The performance of the overall control scheme is experimentally validated by a grid‐connected hybrid microgrid consisting of 10 kWp solar PV, 1 kW wind turbine, 15 kVA biogas engine generator, and 1 kW 6 h VRFB storage. The proposed energy management scheme is scalable and a generalized one that claims to be suitable for large‐scale renewable energy integrated power systems as well. Abstract : Herein, an optimized scheduling of hybrid renewable energy (RE) sources, VRFB storage, and distribution grid is demonstrated to satisfy local load demand management. The cost of energy management is also optimized based on the power shared by multiple RE sources, grid tariff profile throughout the day, and operating cost of the energy sources and storage system.